Lanthanum (III) Selective Electrode Based on 1,10-Diaza-4,7, 13,16-Tetraoxacyclooctadecane-N,Nâ-Diacetic Acid (DACDA) as an Ionophore - Suyanta Suyanta; Susanto Imam Rahayu; Buchari Buchari; Indra Noviandri (Jurnal Matematika & Sains, 2006)
A lanthanum(III) ion selective electrode based on ionophore 1,10-diaza-4,7,13,16-tetraoxacyclooctadecane-N,N-diacetic acid was studied. The electrode was prepared with an inner solution system in a membrane composition that contained an active ionophore 1,10-diaza-4,7-13,16-tetraoxacycloocta decana-N,N-diacetic acid (DACDA), an anionic side potassium tetrakis (4-chlorophenyl) borate (KTCPB), a plasticizer o-nitro phenyl octyl ether (NPOE) and a polyvinyl chloride (PVC) matrix support. A good response was obtained with a slope of 19.53 Â± 1.62 mV/decade and the electrode gave responses with a detection limit of 3.92x10-6 M. The measurement range was wide (10-5-10-1 M) and the responses time was about 27 seconds. The electrode could measure lanthanum ion with a few interfering alkali, earth alkali and transition elements.